A Hermeneutical Reading of a Secularized World: : The Second Vatican Council and its Influence on Graham Greene’s Catholic Imagination - Beatriz Valverde (International Journal of English Studies, 2025)
The Second Vatican Council and its hermeneutical dynamics of a progressively secularized modern world had a profound impact on the lives of millions. Drawing upon Jüri Lotman’s theory of cultural semiotics, this article aims first to examine Vatican II as an attempt to incorporate frontier discourses into the centrality of the Catholic Church semiosphere, i.e., the Vatican, mainly regarding moral theology and social doctrine. Within this context, I will analyze the impact of the Council on Graham Greene’s Catholic imagination. Through the study of Greene’s correspondence to editors of different publications concerning such controversial topics as birth control, the right to die, and the role of the Church in the political upheavals in Central and Latin America, I will argue that Greene identified himself with Vatican II’s desire to articulate Catholicism in new ways. Additionally, the analysis of his correspondence to the press will offer further insights into how Greene weaves these topics into his literary work. In this sense, Greene embodies the theological issues of the Council in his own religious and literary imagination and illustrates its reception by Roman Catholics in the 1970s and 1980s.